2011
DOI: 10.1136/emj.2010.109702
|View full text |Cite
|
Sign up to set email alerts
|

Cardioversion of acute atrial fibrillation in the emergency department: a prospective randomised trial

Abstract: EC was more effective in patients with acute AF and resulted in a shorter length of stay in the ED than PC. Adverse events were small in number and transient in both groups of patients. Clinical trials registration number NCT00933634.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 25 publications
4
24
1
1
Order By: Relevance
“…Effectiveness of ECV in our registry was comparable to that reported in the literature (78-97%) [7][8][9][10]. Although some data suggest that in AF, 200 J energy should be started, especially in non--paroxysmal AF [11], we show that about 160 J energy may also be effective.…”
Section: Discussionsupporting
confidence: 86%
“…Effectiveness of ECV in our registry was comparable to that reported in the literature (78-97%) [7][8][9][10]. Although some data suggest that in AF, 200 J energy should be started, especially in non--paroxysmal AF [11], we show that about 160 J energy may also be effective.…”
Section: Discussionsupporting
confidence: 86%
“…During 2 months of follow-up recurrence of AF was observed in about 25% of patients -the rate comparable to previous results [14], and the frequency of rehospitalization was about 19% in the whole group (27.7% in the paroxysmal AF) -in one of the earlier studies 33-35% of patients had recurrent visits on Emergency Department during a 6-months of follow-up [15]. In the Euro Heart Survey on Atrial Fibrillation registry, the rate of rehospitalization within 1 year was between 41% (first detected AF episode) and 54% (paroxysmal AF) [9].…”
Section: Discussionsupporting
confidence: 89%
“…No serious adverse events were recorded. In 2012 Bellone et al 19 reported a clinical trial involving 121 patients who underwent DCCV in the ED facilitated by procedural sedation with propofol provided by emergency physicians. The primary outcome for this trial was the success rate of cardioversion for acute AF using DCCV versus propafenone.…”
Section: Discussionmentioning
confidence: 99%